A Review on the Use of Agriculture Waste Material as Lightweight Aggregate for Reinforced Concrete Structural Members. (21st December 2014) - Mo, Kim Hung; Alengaram, U. Johnson; Jumaat, Mohd Zamin
Abstract : The agriculture industry is one of the main industries in the Southeast Asia region due to its favourable conditions for plantations. In fact, Southeast Asia region is the world's largest producer of palm oil and coconut. Nevertheless, vast plantation of these agriculture products leads to equally large amount of waste materials emanating from these industries. Previously, researchers have attempted to utilize the resulting waste materials such as oil palm shell, palm oil clinker, and coconut shell from these industries as lightweight aggregate to produce structural grade lightweight aggregate concrete. In order to promote the concept of using such concrete for actual structural applications, this paper reviews the use of such agriculture-based lightweight aggregate concrete in reinforced concrete structural members such as beam and slab, which were carried out by researchers in the past. The behaviour of the structural members under flexural, shear, and torsional load was also summarized. It is hoped that the knowledge attained from the paper will provide design engineers with better idea and proper application of design criteria for structural members using such agriculture waste as lightweight aggregate.